Analisis FXS (Foreign Exchange Subscriber) Port Pada IPPBX (Internet Protocol Private Branch Exchange) - Dyah Anggraini (Jurnal Jaringan Telekomunikasi, 2020)
PBX is a telephone communication connection device that is commonly used in buildings that require a telephone connection. However, some PBX products cannot be directly connected to analog telephones, so they require a module called an S2 module. S2 module can converts the port on the PBX to an FXS port that can be connected to an analog phone. Apart from PBX, there is ITG which can be used as telephone line communication. However, ITG already has an FXS port so it does not require additional modules. In Indonesia, there are standard provisions for the use of analog telephone communication devices which have been regulated in SNI for analog telephones. This research examines analog telephone communication devices according to SNI in Indonesia. The results of this test show the TA400 and MyPBX Standard at the impedance value when the on-hook state gets an average value of 64 K?, when the off-hook condition averages a value of 343 ?, the AC voltage test when the call comes on average gets a value of 343 ?. a value of 60 VAC, which means that it meets the SNI standard.